Microbiological changes after periodontal therapy in diabetic patients with inadequate metabolic control - Silva-boghossian, Carina Maciel (2014)
The present study investigated the effect of non-surgical periodontal treatment (SRP) on the composition of the subgingival microbiota of chronic periodontitis (CP) in individuals with type 2 diabetes (DM2) with inadequate metabolic control and in systemically healthy (SH) individuals. Forty individuals (20 DM2 and 20 SH) with CP underwent full-mouth periodontal examination. Subgingival plaque was sampled from 4 deep sites of each individual and tested for mean prevalence and counts of 45 bacterial taxa by the checkerboard method. Clinical and microbiological assessments were performed before and 3 months after SRP. At baseline, those in the DM2 group presented a significantly higher percentage of sites with visible plaque and bleeding on probing compared with those in the SH group (p < 0.01). Those in the DM2 group presented significantly higher levels of C. rectus and P. gingivalis, and lower prevalence of P. micra and S. anginosus, compared with those in the SH group (p ≤ 0.001). At the 3-month visit, both groups showed a significant improvement in all clinical parameters (p < 0.01). Those in the DM2 group showed significantly higher prevalence and/or levels of A. gerencseriae, A. naeslundii I, A. oris, A. odontolyticus, C. sputigena, F. periodonticum, and G. morbillorum compared with those in the SH group (p ≤ 0.001). However, those in the DM2 group showed a significant reduction in the levels of P. intermedia, P. gingivalis, T. forsythia, and T. denticola (p ≤ 0.001) over time. Those in the SRP group showed improved periodontal status and reduced levels of putative periodontal pathogens at 3 months’ evaluation compared with those in the DM2 group with inadequate metabolic control.